The Total Network Capacity of Wireless Mesh Networks for IoT Applications - Ar-Reyouchi, El Miloud; Lamrani, Yousra; Benchaib, Imane; Ghoumid, Kamal; Rattal, Salma (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Computing and measuring the total capacity of a data network are a remarkably difficult problem. These metrics are directly linked to the available bandwidth to each wireless internet of things (IoT) device of the network. In this paper, the authors study the performance metrics associated with capacity traffic in multi-hop wireless mesh networks (WMNs). It is dedicated to Internet access assuming a time division multiple access (TDMA). They focus simultaneously on three key operating metrics, the total network capacity (TNC), total application network capacity (TANC), and the Average message time (AMS). They also analyze how parameters such as forward error correction (FEC) and acknowledgments (ACK) affect the overall network capacity under different operating conditions. Theoretical network capacity for WMNs, in this paper, is explored to draw attention to the number of open research issues